Evaluation of anti-tumor activity of metformin against Ehrlich ascites carcinoma in Swiss albino mice. Issue 1 (2nd January 2019) - Elkhawaga, Om-Ali; Gebril, Sara; Salah, Nivin
ABSTRACT: In many types of malignancy, ascites is a prognostic sign of advanced stage, with a survival rate of 11% for patients with ascites more than 6 months. Currently, combination therapy has become the base of cancer treatment. However, cytotoxicity to normal tissue is the major limitation of current combined drugs. In this study, Ehrlich ascites carcinoma (EAC) inoculated into mice was targeted with three consecutive doses of metformin, a safe drug with an anti-cancer effect. To test its suitability as a potential safe candidate against EAC cells for later combination therapy in comparable with cisplatin as a reference anti-neoplastic drug. The group that received metformin developed less malignant ascites than the control group. Metformin induced cellular quiescence in the EAC cells by upregulation of cyclin-dependent kinase inhibitor 1 (p21) expressions as cisplatin acted. Cell cycle analysis confirmed the quiescence state of the EAC cells treated with metformin or cisplatin. Furthermore, metformin-induced toxicity to EAC cells through elevation of reactive oxygen species levels (ROS). Therefore, metformin can be a suitable candidate for future combination with a low dose of cisplatin to treat the aggressiveness of EAC cells.